Lithological and Topographic Impact on Soil Nutrient Distributions in Tectonic Landscapes: Implications for Pleistocene Human-Landscape Interactions in the Southern Kenya Rift - Kübler, S.; Rucina, S.; Aßbichler, D.; Eckmeier, E.; King, G. (Frontiers in Earth Science, 2021)
Tectonically active regions are characterized by complex landscapes comprising soils with heterogeneous physicochemical properties. Spatial variability of nutrient sources enhances landscape biodiversity and creates heterogeneous habitats potentially attractive for animals and humans. In this study, we analyze the role of geological processes in the distributions of soil nutrients in the southern Kenya Rift, a key region in the interpretation of early human-landscape interactions. Our aim is to determine how spatial variations in rock chemistry, as well as topographic gradients and localized zones of rock fracturing from tectonic faulting determine the distributions of plant-available soil nutrients in soils. We hypothesize that present-day soil nutrient levels reflect the long-term chemical and geomorphological characteristics of the landscape and underlying parent material, and that regions with high nutrient availability occur along pathways correlating with locations of hominin fossil sites. Analyses of 91 topsoil samples from the main geological units show that Calcium (Ca) deficiencies predominately occur in shallow soils developed on trachytic volcanic rocks and granitic gneisses, while high Ca levels are associated with basaltic parent material and sedimentary deposits of mixed sources. XRF analysis of rock samples confirms that CaO levels in trachyte rocks are significantly lower than those in basalts, and Ca mobilization in basalt is more effective than in trachyte. Along two toposequences in densely faulted basaltic and trachytic rocks, we observed slope dependent soil nutritional gradients and a systematic increase of the concentrations of Ca, Mg and SOC in topsoils of colluvial sediments downslope of active normal faults. Known hominin sites in the region are located either along corridors of long-term Ca availability or at short-term nutrient hotspots potentially related to active CO2 degassing along active fault zones. This implies a strategic advantage of Ca-rich regions for hominin subsistence strategies, such as provision of predictable constraints on the distribution and mobility of grazing animals in complex tectonic landscapes. Our study implies that geological processes impact nutrient distributions in the southern Kenya Rift. Results of this study have further implications for understanding the role of soils in the interpretation of hominin-landscape interactions in the early stages of human evolution.